Novel Nested Direct PCR Technique for Malaria Diagnosis Using Filter Paper Samples - Fuehrer, Hans-Peter (American Society for Microbiology, 2011)
The use of direct nested PCR enables the detection of Plasmodium spp. from blood samples collected on filter papers without requiring the time-consuming procedures associated with DNA extraction. Direct PCR provides a rapid, highly sensitive, and cost-effective alternative to diagnosing malaria using filter paper samples and standard nested PCR.